Calculating Value in Hand and Wrist Care: A Systematic Review on the Current Literature - Zachary Chen, BS; Mithil Gudi, BS; Alex Lindahl, BS; Charles S. Day, MD, MBA (Journal of Hand Surgery Global Online)
Purpose: Global health care systems are shifting toward value-based care models, with the hand and wrist field presenting a notable opportunity to enhance quality and efficiency because of large patient volumes, a variety of pathologies, and diversity in treatment options. This systematic review aimed to investigate the literature on calculations of value between different treatment options in hand and wrist care. Methods: Adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, two reviewers searched three databases to identify, screen, and evaluate research articles within hand and wrist care comparing the value between treatment groups based on real-world clinical data. Results: Nineteen of 181 hand and wrist articles screened met our predetermined inclusion criteria. Studies primarily employed the EuroQol 5-Dimension survey for quality metrics with the payer or societal cost perspective. The incremental cost-effectiveness ratio formula was the most used value calculation. The majority of included studies originate from Europe. Studies assessing distal radius fracture care highlighted reduced imaging strategies as more cost effective than traditional methods and bandaging as more cost effective than rigid immobilization. Studies assessing scaphoid fractures identified immediate magnetic resonance imaging intervention to outperform standard care and cast treatment combined with early fixation to be superior to standalone surgery or no treatment. Conclusions: Global literature on value-based comparative studies in hand and wrist care demonstrates variability in methodology, limiting direct comparisons. Most real-world studies were conducted within single-payer systems, highlighting the potential for further investments in value analysis protocols in multipayer systems. Clinical relevance: Establishing a standardized methodology for value assessment, will enable better comparisons and improvements in hand and wrist care. As global health care costs continue to rise, conducting research that identifies high-value care across diverse health care systems is essential to ensure sustainable, effective, and patient-centered care for all stakeholders.